Nuclear physics experiments with ion storage rings - Litvinov, Yuri A.; Blaum, Klaus; Winckler, Nicolas (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
In the last two decades a number of nuclear structure and astrophysics experiments were performed at heavy-ion storage rings employing unique experimental conditions offered by such machines. Furthermore, building on the experience gained at the two facilities presently in operation, several new storage ring projects were launched worldwide. This contribution is intended to provide a brief review of the fast growing field of nuclear structure and astrophysics research at storage rings.
Gesehen am 18.05.2021